IMPLEMENTATION OF THE BANDUNG MASAGI POLICY IN THE MUNICIPALITY OF BANDUNG INDONESIA - Engkus; Fadjar Tri Sakti; Andika Muhamad Rafi Annaafi; Soni Gunawan Somali (International Journal of Social Science, 2021)
The implementation of this policy is motivated by the still occurrence of problems in the educational environment such as in the school environment where cases of bullying or hazing still often occur to students, especially those who have just entered school so that seniority actions can have a negative impact on students. Therefore, a character education policy based on local wisdom of Sundanese culture was created, named Bandung Masagi with the aim of growing the perfect character of students. The purpose of this study was to identify and describe the implementation of the Bandung Masagi policy. The research method used by the researcher is a descriptive method with a qualitative approach. Data collection techniques used: observation, interviews and literature study. The results of the study reveal that the implementation of Bandung Masagi's policy has been running, but not yet optimal, dimensionally there are still obstacles. In terms of Policy Content, Policy Executors & Target Groups and Environment The novelty of this research is a policy of character education based on Sundanese local wisdom.